2011
DOI: 10.5152/tjh.2011.01
|View full text |Cite
|
Sign up to set email alerts
|

The importance of protein profiling in the diagnosis and treatment of hematologic malignancies

Abstract: Proteins are important targets in cancer research because malignancy is associated with defects in cell protein machinery. Protein profiling is an emerging independent subspecialty of proteomics that is rapidly expanding and providing unprecedented insight into biological events. Quantitative assessment of protein levels in hematologic malignancies seeks a comprehensive understanding of leukemiaassociated protein patterns for use in aiding diagnosis, follow-up treatment, and the prediction of clinical outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 124 publications
1
3
0
Order By: Relevance
“…No premalignant cases were investigated by Hu et al 62 Xie et al 63 have identified proteins in cells separated from saliva from four subjects with oral squamous cell carcinoma of tongue only and have not provided any diagnostic techniques. Almost all studies were done by mass spectroscopic techniques with the inherent disadvantages pointed out by Mohamed et al 60 The present study clearly shows that our technique of HPLC-LIF protein profiling-PCA pattern analysis of the profiles can provide a noninvasive, relatively fast, and sensitive method for screening for early detection. The same technique can, obviously, be used for monitoring the effectiveness of therapy and follow up for early detection of any regression after apparent cure.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…No premalignant cases were investigated by Hu et al 62 Xie et al 63 have identified proteins in cells separated from saliva from four subjects with oral squamous cell carcinoma of tongue only and have not provided any diagnostic techniques. Almost all studies were done by mass spectroscopic techniques with the inherent disadvantages pointed out by Mohamed et al 60 The present study clearly shows that our technique of HPLC-LIF protein profiling-PCA pattern analysis of the profiles can provide a noninvasive, relatively fast, and sensitive method for screening for early detection. The same technique can, obviously, be used for monitoring the effectiveness of therapy and follow up for early detection of any regression after apparent cure.…”
Section: Resultssupporting
confidence: 63%
“…59,60 The reversed phase HPLC with ultra-sensitive LIF detection has been suggested as the best technique for diagnostic applications of protein profiling due to its superior resolution, high-time efficiency, high-detection capacity, and sensitivity. 60 The combination of the highly sensitive LIF (which has advantages such as limited stray light effects, low background and accurate focusing capacity of the excitation source on to the micro-bore capillary leading to the excitation of picoliter amounts of samples without any loss of excitation energy etc.) and highly efficient HPLC enables easy detection of the ultra trace biomolecules in complex physiological samples.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the albumin peak, in 20 mL of 500 times diluted serum gives a signal of .1 V. The noise level in our system is 0.001 V, and this gives a limit of detection (in these runs) of a few femtomoles. We have shown (10)(11)(12)(13)(14)(15)(16)(17) that the sensitivity of the system can be increased by 2-3 orders of magnitude, if necessary, by appropriate choice of experimental parameters (higher laser power, multi-passing laser, collecting more fluorescence with better optics, etc.) and detection system (higher PMT voltage, more signal amplification, use of band pass filters in place of monochromator, etc.).…”
Section: Methodsmentioning
confidence: 99%
“…Several groups are working at present in this area using different techniques like 2-D gel electrophoresis, MALDI-TOF mass spectrometry, HPLC-MS, SELDI-MS, Bio-bar codes, and HPLC-LIF. Each of these methods has got its own advantages and disadvantages as has been pointed out earlier [14].…”
Section: Introductionmentioning
confidence: 99%